1990
DOI: 10.1177/019459989010300310
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Hemostatic Assessment of the Adenotonsillectomy Patient

Abstract: Intraoperative or postoperative hemorrhage in the patient who has undergone an adenotonsillectomy because of an unrecognized hemostatic defect may increase morbidity and can be potentially life-threatening to the patient in what should be a "routine" procedure. Preoperative identification of occult hemostatic abnormalities, coupled with perioperative management directed at correcting the effects of the defects, should serve to reduce the incidence of this distressful complication. Routine use of preoperative l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 33 publications
1
41
0
1
Order By: Relevance
“…Including such analysis in Introduction Tonsillectomy remains one of the most commonly performed surgical procedures in the fi eld of Otorhinolaryngology. Th e most serious complication is postoperative hemorrhaging accompanied by a 2-4% risk of substantial bleeding [1]. A similar incidence could be observed in a previous retrospective study performed at the Department of Otorhinolaryngology, University Hospital of Vienna.…”
Section: Discussionsupporting
confidence: 80%
“…Including such analysis in Introduction Tonsillectomy remains one of the most commonly performed surgical procedures in the fi eld of Otorhinolaryngology. Th e most serious complication is postoperative hemorrhaging accompanied by a 2-4% risk of substantial bleeding [1]. A similar incidence could be observed in a previous retrospective study performed at the Department of Otorhinolaryngology, University Hospital of Vienna.…”
Section: Discussionsupporting
confidence: 80%
“…Controversies exist in the preoperative evaluation of patients for tonsillectomy especially regarding hemorrhage and its control (Bolger et al, 1990;Gabriel et al, 2000;Asaf et al, 2001) but this paper would not dwell on these issues.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the otolaryngology literature have shown that there is no significant increase in the risk of post-tonsillectomy bleeding in patients with abnormal coagulation studies compared to those with normal studies.1-3 However, some studies have shown that an abnormal preoperative coagulation profile may identify those patients at increased risk for perioperative bleeding. [4][5][6] While most of these studies have used perioperative bleeding as the endpoint to assess the usefulness of preoperative screening, only a few have performed detailed coagulopathy evaluations to define the bleeding disorder. 4,7 To determine if preoperative screening is useful in identifying a bleeding disorder, we retrospectively reviewed the coagulopathy evaluations of 131 children referred for a prolonged preoperative aPTT.…”
mentioning
confidence: 99%